IMPLEMENTASI METODE RAPID APPLICATION DEVELOPMENT PADA PENGEMBANGAN SISTEM KELOLA DATA KALIBRASI DI PERCETAKAN GRAMEDIA - Gunadi, Goldie (ISTEK WIDURI, 2023)
The Rapid Application Development (RAD) model is an object-oriented software development model that aims to shorten information system development time. Calibration is an activity of determining the correctness value and checking and adjusting the accuracy of measuring instruments with national standards and/or international standards. As a company engaged in the printing sector, PT Gramedia uses a variety of measuring instruments that need to maintain their level of accuracy, so a calibration process needs to be carried out regularly. The General Affairs (GA) section is responsible for carrying out this calibration activity with the help of outside vendors. Currently, the administrative process for calibration activities is still carried out conventionally, causing various problems that can result in disruptions to production process activities and a decrease in the quality of the printed products produced. The purpose of this research is to develop a web-based information system by applying the RAD development model to speed up the process and the application of the MVC method using the Codeigniter framework in the application coding process. From the test results using the black box method, the resulting calibration administration system can run well in accordance with user expectations.